Level of Knowledge, Attitudes and Behavior of Pregnant Women Towards The Frequency of ANC Visits In Rangkasbitung Health Center Working Area - Prajawati, Eka; Faulina, Riza (Jurnal Obstretika Scientia, 2023)
Background: Antenatal visit coverage has increased by 88.13% from the set target of 85%, reflecting improvements in maternal health indicators. While nationally meeting targets, 17 provinces, including West Papua and Papua, lag behind. Despite the increase in coverage from 2020 to 2021, disparities persist, according to Indonesian Ministry of Health data. Research Objective: Assessing pregnant women's knowledge, attitudes, and behaviors regarding antenatal care (ANC) frequency in Rangkasbitung Community Health Center. Research Methods: Employing a cross-sectional design with a sample size of 81 respondents, utilizing a sample size formula. Research Results 81.3% of respondents completed ANC visits, with 41.3% exhibiting good knowledge, 91.3% displaying positive attitudes, and 81.3% demonstrating favorable behaviors. Statistical tests revealed no significant relationship between knowledge or attitudes and ANC visit frequency. However, a significant association was found between attitudes and ANC visit frequency. Conclusion and Suggestion: While good knowledge and attitudes may suggest better ANC visit adherence, statistical tests indicate no significant relationship. Various factors such as personal experiences, cultural influences, media, education, and religious beliefs shape pregnant women's behaviors regarding ANC visits. Public health interventions should consider these multifaceted factors for effective implementation..